Financial Frictions and Sources of Business Cycle - Taheri Sanjani, Marzie (IMF Working Papers; Working Paper ;, 2014)
This paper estimates a New Keynesian DSGE model with an explicit financial intermediary sector. Having measures of financial stress, such as the spread between lending and borrowing, enables the model to capture the impact of the financial crisis in a more direct and efficient way. The model fits US post-war macroeconomic data well, and shows that financial shocks play a greater role in explaining the volatility of macroeconomic variables than marginal efficiency of investment (MEI) shocks.